Geography teachers' stories of sustainability: an introduction to narrative research - Brooks, Clare (International research in geographical and environmental education, 2016)
Geography teacher recruitment and retention is an important issue for the future of geography education. This Special Issue of IRGEE tackles this issue head on by focusing on geography teachers' narratives about their experiences of teaching geography, and asking why some geography teachers stay in the profession while others leave. This paper serves as an introduction to this Special Issue, outlining why adopting a narrative approach enables us to gain a deeper understanding of the experience of teaching geography, and why it is important to understand the experience of those teachers who stay in the profession. The theme that emerges from this collection of papers is the significance of the interplay between context and identity when seeking to understand geography teachers' work, and in particular why subject identity matters. These themes are echoed in the other papers of this Special Issue, indicating that now there is sufficient evidence for geography education to take the issue of teacher subject identity seriously, and for further research to consider the implications for initial and continuing teacher education.